Distribution of sensory nerve endings around the human sinus tarsi: a cadaver study. Issue 4 (29th January 2014) - Rein, Susanne; Manthey, Suzanne; Zwipp, Hans; Witt, Andreas
Abstract The aim of this study was to analyse the pattern of sensory nerve endings and blood vessels around the sinus tarsi. The superficial and deep parts of the fat pads at the inferior extensor retinaculum (IER) as well as the subtalar joint capsule inside the sinus tarsi from 13 cadaver feet were dissected. The distribution of the sensory nerve endings and blood vessels were analysed in the resected specimens as the number per cm2 after staining with haematoxylin‐eosin, S100 protein, low‐affinity neurotrophin receptor p75, and protein gene product 9.5 using the classification of Freeman and Wyke. Free nerve endings were the predominant sensory ending (P < 0.001). Ruffini and Golgi‐like endings were rarely found and no Pacini corpuscles were seen. Significantly more free nerve endings (P < 0.001) and blood vessels (P = 0.01) were observed in the subtalar joint capsule than in the superficial part of the fat pad at the IER. The deep part of the fat pad at the IER had significantly more blood vessels than the superficial part of the fat pad at the IER (P = 0.012). Significantly more blood vessels than free nerve endings were seen in all three groups (P < 0.001). No significant differences in distribution were seen in terms of right or left side, except for free nerve endings in the superficial part of the fat pad at the IER (P = 0.003). A greater number of free nerve endings correlated with a greater number of blood vessels. The presence of sensory nerve endings between individual fat cells supports the hypothesis that the fat pad has a proprioceptive role monitoring changes and that it is a source of pain in sinus tarsi syndrome due to the abundance of free nerve endings.